Strengthening the Subjective Well-being of People Living with HIV Through Gratitude Intervention in the Mahakam Plus Peer Support Group in Samarinda City - Hidayati, Diajeng Laily; Dewi, Lharasati; Indriani, Dewi; Abdi, Andi Muhammad (Universitas Muhammadiyah Surakarta, 2025)
People Living with HIV (PLHIV) often find themselves trapped in negative emotional states, such as feelings of distress and loss of life purpose. They frequently experience shame, marginalization, and a lack of motivation due to the stigma attached to their condition. These circumstances tend to hinder the achievement of optimal subjective well-being for PLHIV. Gratitude intervention is one program that can be implemented to enhance the subjective well-being of PLHIV. This community service program aims to improve the subjective well-being of PLHIV through gratitude intervention. The method used in this activity is Participatory Action Research (PAR), involving the active participation of 30 participants, including stakeholders, the Mahakam Plus KP team, and PLHIV at every stage of the program, from building rapport, conducting a needs assessment, planning the program, implementing it, assigning tasks, and evaluating outcomes. The intervention sessions include introductions, material presentations, video viewing, and gratitude journaling. The results indicate that after participating in the gratitude intervention program, PLHIV feel more grateful and are better able to accept their condition. Therefore, this program needs to be conducted continuously to consistently support the subjective well-being of PLHIV.